Pengaruh Profitabilitas, Leverage, Likuiditas, Ukuran Perusahaan, dan Komite Audit Terhadap Laporan Keberlanjutan - Maulana, Arif; Maharani, Novera Kristiati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyze the effects of profitability, leverage, liquidity, firm size, and the audit committee on sustainability reporting in energy-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research is motivated by the increasing demand for corporate transparency and accountability regarding economic, environmental, and social impacts. The study uses secondary data from annual reports and sustainability reports, employing purposive sampling. The data were analyzed using multiple linear regression, corrected with the Newey-West method to account for violations of classical assumption tests. The results show that profitability, firm size, and the audit committee have positive and significant effects on sustainability reporting, while liquidity has a negative and significant effect. Meanwhile, leverage does not affect sustainability reporting. These findings support stakeholder theory, which posits that companies with strong financial performance and effective governance tend to enhance the disclosure of sustainability information. This study is expected to inform management and investors in their decision-making.